Experiment modeling tool development wheels related to the control advance for video tracker analysis - - Harviyani; - Asrizal (PILLAR OF PHYSICS, 2020)
The concepts explained by Physics can be the basis for the development of new disciplines. Theory explains the results of experiments carried out and subsequent experiments.Observations prove that experiments using manual tools still have many shortcomings . Physics parameters that can be displayed are still a bit of a weakness.This problem can be overcome by modeling tools that analyzed the video using a tracker.This study aims to determine the accuracy, accuracy, and resolution of controlling the speed of a DC motor, determine the performance specifications of the related wheel experimental model modelingtool, determine the accuracy and accuracy of the related wheel circular motion modeling tool, determine the physical magnitude and influence of each of the wheel relations of the modeling tool. This research is classified into laboratory experiment research method. Laboratory experiments are researches that apply science into a design to get performance as expected. Direct measurement is done by varying the speed and type of wheel connection. Indirect measurements are carried out analysis using a tracker software with the resulting data is linear velocity and angular velocity. Data analysis carried out revealed four research results. The performance specifications which consist of a circular motion modeling tool related to the length of 35 cm, width 5 cm and height 20 cm by controlling, average value of accuracy and accuracy of DC motor rate control are 99.06% and 99.55%, respectively. Accuracy value for linear velocity is 99.35%, accuracy at angular velocity is 99.63%, and the accuracy value of each relationship is> 95%. Tangent wheel has the same linear velocity value, different angular velocity , and opposite wheel rotation direction . Centralized wheels have different linear speeds, angular speed and direction of wheel rotation are the same. The wheels connected by ropes have the same linear velocity and direction of rotation of the wheels, different angular velocity values.